Navigating the Unprecedented: Working Remotely Unexpectedly - Matt Sowcik; Megan Stein (EDIS)
Working from an alternative location can be a daunting adjustment. Ensuring personal well-being and productivity through unexpected times takes a proactive partnership between employers and employees. This new 3-page publication of the UF/IFAS Department of Agricultural Education and Communication provides some best practices for personal well-being and productivity while working remotely. Written by Megan Stein and Matthew Sowcik.